v.2 - Sharma, R .K; Twari, S.K. (New Delhi, 2002)
Central India comprising of modern Madhya Pradesh, Chhattisgarh and adjoining regions strategically forming the heartland of our country has played a key-role in the development of historical and cultural traditions of the nation. It has been the playground of interacting political and cultural forces passing from north to south, east to west and vice versa in all ages of Indian history. Interaction led to experimentation in diverse spheres of cultural life and in this process, the tribal population migrating to this part of the country in different phases of its history as well as those inhabiting the region from the earliest times had an invaluable contribution. It may be admitted that the study of the history and culture of a nation is never complete without having a thorough knowledge of the history and cultural growth of its tribes. Keeping this in view, an attempt has been made in this work to present an exhaustive and careful study of the tribal history of Central India from the earliest times till date, and their cultural contributions and growth. The tribal culture of India has always been interpreted as something alien from the main stream of Indian culture and thought, whereas the historical truth is otherwise. These and other allied problems have been raised in the present study in an effort to remove prevailing misconceptions about the culture of tribal communities of India in general and Central India in particular. This book in three volumes is an attempt to provide a historical background to trace cultural roots of the nation in a truly scientific spirit. The work thus fulfills a long-felt need of the scholars interested in getting a first hand, authoritative and up-to-date account of the tribal heritage of Central India at one place.
Volume 2. Tribal communities of ancient and medieval periods.
Keywords: Tribes